What do Children tell us? Listening and observation pointing directions - Hardalla do Valle; Angela Bersch; Eliane Piske (Universidade Federal do Norte do Tocantins, 2023)
This article aims to address the relevance of listening and observation in the work built with children. To this end, we will present a project carried out in a public school, of Early Childhood Education, in the city of Rio Grande-RS. The foundation of this research was qualitative, composed of grounded data theory and project methodology. Among the main results obtained, we highlight that belonging and emotions are fundamental factors for a shared and meaningful educational process. We also found that children are open to communicating their thoughts, desires and desires. In this sense, the sensitive exercise of listening and observation proves to be essential for a pedagogical work that aims to be carried out with respect for the protagonism of children.